1999
DOI: 10.1046/j.1365-2036.1999.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an inhibitor of matrix metalloproteinases on colonic inflammation in a trinitrobenzenesulphonic acid rat model of inflammatory bowel disease

Abstract: Dosing rats with TNBS-induced colitis using sulphasalazine or marimastat produced a significant reduction in tissue injury and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
2
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 20 publications
1
48
2
2
Order By: Relevance
“…The studies published so far have confirmed the overexpression of MMPs, including MMP-3 and -9, both in ulcerative colitis and in Crohn's disease (CD). Alterations of MMPs activity depending on the degree of disease exacerbation have been observed in animal models with induced bowel inflammation [11,12]. Elevated concentrations of MMPs have also been noted in biopsy specimens collected from inflamed fragments of the alimentary tract [1,2,13,14].…”
Section: Discussionmentioning
confidence: 92%
“…The studies published so far have confirmed the overexpression of MMPs, including MMP-3 and -9, both in ulcerative colitis and in Crohn's disease (CD). Alterations of MMPs activity depending on the degree of disease exacerbation have been observed in animal models with induced bowel inflammation [11,12]. Elevated concentrations of MMPs have also been noted in biopsy specimens collected from inflamed fragments of the alimentary tract [1,2,13,14].…”
Section: Discussionmentioning
confidence: 92%
“…Mesenchymal cells were identified as major producers of MMP-1 and -2 [6] . MMPs were implicated in the tissue destruction associated with inflammatory diseases and the role of MMPs in the pathogenesis of inflammatory bowel disease was also confirmed through improvement of experimentally induced colitis after treatment with a matrix metalloproteinase inhibitor [21] . Apart from protease-inhibitory action TIMP-1 serves [22,23] .…”
Section: Discussionmentioning
confidence: 94%
“…Considering that the IC 50 of Marimastat against MMP-13 is 4.59 nM, the margin between potency and toxicity is only ϳ2-fold. Marimastat also has nanomolar potency against other MMPs, with an IC 50 of 1.94 nM and 2.10 nM against collagenase 1 (MMP-1) and collagenase 2 (MMP-8), respectively (39).…”
Section: Discussionmentioning
confidence: 99%